Ultrathin Polyoxometalate Coating as the Redox Shuttle for Acid‐Free Electrochromic Polymer Capacitive Windows. (7th March 2019) - Wang, Shi‐Ming; Kim, Younghoon; Kim, Byeonggwan; Han, Minsu; Kim, Eunkyoung
Abstract: Polyoxometalate is explored as a redox shuttle for non‐electrochromic charge‐balancing material of the conjugated polymer (CP)‐based electrochromic window (ECW). H3 PW12 O40 is electrochemically deposited on a TiO2 nanoparticle film that is coated on a fluorine doped tin oxide glass. The content of PW12 is increased as the TiO2 film is thicker. The PW12 ‐coated TiO2 film (PWTNF) is applied as a counter electrode (CE) of a CP‐based ECW in an ionic liquid electrolyte, to increase the potential distribution at the CP‐coated working electrode, thereby decreasing the operation voltage of the ECW. This could be ascribed to the function of PW12 as an electron acceptor and redox shuttle that allows effective charge transport from/to the CE and nearby TiO2 nanoparticles. For the optimized ECW with PWTNF as a CE, the maximum optical contrast is obtained at the applied voltage of 1.5 to −2.0 V (68%), along with long cyclability (2500 cycles), bistability (> 2.35 h) and UV stability (> 60 h). The ECW with PWTNF exhibits reproducible capacitive properties, along with high figure of merit for color change with a high power output, in acid‐free electrolyte for the first time. Abstract : Polyoxometalate (POM) is explored as a redox shuttle for non‐electrochromic charge‐balancing of conjugated polymer‐based electrochromic windows (ECW). The operate applied voltage is decreased to get the maximum optical contrast. The ECW with POM‐coated TiO2 film as the counter electrode exhibits reproducible capacitive properties, along with a high figure of merit for color change.